Moving beyond binary sex: understanding the victimization and offending patterns of LGBTQ+ people in the United States - Hurst, Y. Gail (Gender and crime, 2024)
Historically, the justice system relied on a binary classification system to understand and treat individuals based on their gender, categorizing them as male or female. By simply defining sex and gender as male or female, the complexities of gender identity and sexual orientation have been overlooked in discussions of crime and victimization in the United States. This chapter aims to shed light on the victimization and offending patterns of gender-nonconforming people in the United States by using research studies, official data, and self-reported data. By examining the rates at which the LGBTQ+ community experience victimization and commit crimes, as well as exploring the reasons behind these patterns, we can gain a better understanding of the challenges faced by this marginalized group.